GENDER JUSTICE VERSUS MALE EGO - Puliappallil, Kochuthresia (Asian Horizons, 2019)
The virtue of justice prompts one to do good to others by a constant and perpetual will. Persons with disposition to justice will have a propensity to respect the dignity of others, their fundamental rights and responsible freedom. It is high time for a paradigm shift from over emphasis on submissiveness and obedience to reciprocal responsibility, interdependence and collaboration. In the Indian religious and cultural context, in our search for ways to foster gender justice, we may have to develop a disposition to non-violence and truth. The moral sense of non-violence is grounded in the holistic goodness of the individuals. Hence, all forms of ill-will towards the opposite gender are injustice. A truthful person will be transparent in one’s own reasoning, honest to others and upright before God. Where there is truth there is mutual strengthening, right relationship, trust and love. A Christian should not only be satisfied with fulfilling the principle of justice, rather be merciful without boundaries. Ethics of solidarity with and accountability for a suffering soul completes the ethics of justice. Women have to contribute to all activities of the society by sharing their skills, virtues, knowledge and wisdom. It is argued that most of the inhuman tendencies of violence and injustice would be eradicated if we strive to inculcate in children from an early stage, a moral concern about right relationships and interdependence.